2016
DOI: 10.2147/opth.s120197
|View full text |Cite
|
Sign up to set email alerts
|

Leber’s hereditary optic neuropathy is multiorgan not mono-organ

Abstract: Leber’s hereditary optic neuropathy (LHON) is a maternally inherited mitochondrial disorder with bilateral loss of central vision primarily due to mitochondrial DNA (mtDNA) mutations in subunits of complex I in the respiratory chain (primary LHON mutations), while other mtDNA mutations can also be causative. Since the first description, it is known that LHON is not restricted to the eyes but is a multisystem disorder additionally involving the central nervous system, ears, endocrinological organs, heart, bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 36 publications
(48 reference statements)
0
35
0
Order By: Relevance
“… 1 LHON is caused by various mutations of mitochondrial DNA, leading to the dysfunction of complex I of the respiratory chain. 2 , 3 It is thought that oxidative stress causes microangiopathic damage to retinal arteries. 4 Although vision loss is the defining characteristic of LHON, damage to other organ systems is seen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 1 LHON is caused by various mutations of mitochondrial DNA, leading to the dysfunction of complex I of the respiratory chain. 2 , 3 It is thought that oxidative stress causes microangiopathic damage to retinal arteries. 4 Although vision loss is the defining characteristic of LHON, damage to other organ systems is seen.…”
mentioning
confidence: 99%
“…LHON is inherited maternally with variable penetrance, affecting males more than females. 3 , 4 , 5 It has been suggested that LHON is a multiorgan disease and may present with various vascular manifestations. Macroangiopathic consequences are seen, including arterial hypertension and aortic disease.…”
mentioning
confidence: 99%
“…[9][10][11][12] Unfortunately, these studies tend to include only small cohorts and investigate a limited number of additional manifestations. Likewise, few studies on mortality have been published.…”
mentioning
confidence: 99%
“…Preliminary results showed the therapy's safety, with minimal adverse effects and quantitative improvement in vision in two of five patients, though it is unclear whether this was due to the success of the vector or the nature of LHON, which has low rates of spontaneous recovery. Larger sample sizes will be required to determine the significance of improvements in the trial (150,151). A previous clinical trial for an intravitreally delivered AAV2.ND4 vector resulted in no adverse effects for the trial's nine patients, with a significant increase in visual acuity in six patients, without a change in retinal nerve fiber thickness (152,153).…”
Section: Inner Retinal Disordersmentioning
confidence: 99%